Count Filippo or, The unequal marriage. A drama in five acts. - Heavysege, Charles, 1816-1876 (Toronto reprint library of Canadian prose and poetry., 1973)
A five-act tragedy in blank verse. The play is founded upon the old problem of an unnatural and ill-omened union between youth and age.